Virtual Chemical Sensor For Classification Of Herb ï¿½ Orthosiphon Stamineus According To Its Geographical Origin. - Chew, O.S.; Ahmad, M.N.; Othman, Prof.Madya Abdul Rahman (2003)
Herbal medicine is an important part of health care to a majority of the world's population.